Kajian Kinerja Lingkungan UKM di Surabaya Menuju Industri Hijau - Ferry Suzanto; Wahyono Hadi (Jurnal Rekayasa Teknologi dan sains, 2019)
Abstract A study on assessing the environmental performances of Small and Medium Enterprises (SMEs) during their production operations is required to reduce the negative effects of their activities. The results of study can be used as a reference to formulate recommendations so that SMEs are able to implement the concept of green industry. The study was focused on getting the data on the efforts, potentials, and obstacles encountered by SMEs related to the policy and environmental aspects. It focused on the activities as follows: (a) determining four SMEs in Surabaya as the objects of study, (b) collecting the data on the efforts, potentials, and obstacles encountered by SMEs, (c) analyzing the research findings to formulate recommendations. The result of research recommended having sustainable review on environmental performance of the production operation of SMEs. The activity of review must be accompanied by development attempt such as educating the concept of green industry to SMEs. Education is emphasized on the materials of technological development of production process and environmental management. It includes water and energy audit method so that SMEs have commitment to waste water production and product quality that is safe for consumer’s health.Keywords: Small Medium Enterprise, Green Industry, Environmental Performance. AbstrakUntuk menekan dampak negatif dari kegiatan UKM, maka dibutuhkan sebuah kajian guna menilai kinerja lingkungan yang dilakukan UKM dalam opersional produksinya. Hasil kajian menjadi acuan perumusan rekomendasi agar UKM mampu mengimplementasikan konsep industri hijau. Kajian dikhususkan untuk mendapatkan data tentang upaya, potensi, dan kendala yang dihadapi perusahaan terkait aspek lingkungan dan kebijakan. Penelitian berfokus pada kegiatan: (a) penetapan 3 (tiga) UKM di Surabaya sebagai obyek kajian, (b) pengumpulan data upaya, potensi, dan kendala UKM, dan (c) melakukan analisis terhadap hasil temuan lapangan sebagai bahan merumuskan rekomendasi. Hasil penelitian merekomendasikan agar kajian kinerja lingkungan dalam operasional produksi yang dilakukan UKM dilaksanakan secara kesinambungan. Kegiatan kajian harus dibarengi dengan upaya pembinaan, berupa edukasi konsep industri hijau kepada para pelaku UKM. Edukasi dikhususkan pada materi tentang peningkatan perkembangan teknologi proses produksi dan manajemen lingkungan. Termasuk tentang metode audit energi dan air, sehingga pelaku UKM memiliki komitmen pada produksi nir limbah, dengan jaminan produk yang aman bagi kesehatan konsumen. Kata Kunci: Usaha Kecil Menengah, Industri Hijau, Kinerja Lingkungan